(untitled) (Research, Society and Development, 2020)
Cheese bread is a traditional food product from Minas Gerais and the addition of different ingredients contributes to the improvement in nutritional quality. Chia (Salvia hispanica L.) and flaxseed (Linum usitatissimum L.) are natural sources of omega-3, fiber, and protein. In this perspective, in the present work, cheese bread was added with chia and flaxseed to contribute significantly to the improvement of nutritional value. Three types of cheese bread were developed, being: traditional (PQT), chia (PQC), and flaxseed (PQL), which were sensorial analyzed for acceptance, preference, and purchase intention and by instrumental methods as to color and texture. The PQT showed better acceptance by the tasters with emphasis on odor, color, flavor, and overall impression. For the purchase intention test, PQT was the one with the highest scores, followed by PQL and PQC. The ΔE * value was 21.89, showing that the human eye is able to perceive the difference in color between the formulations. The highest values ​​of firmness were for the PQL (27.18 N) and PQC (25.74 N), which differed statistically from the PQT with a firmness value equal to 21.53 N. As for the ordering test, it was found that there was no difference preferably between samples. Cheese bread with chia and flaxseed have shown as good acceptance as the traditional and can be used as promising alternatives for people looking for a healthy diet. Moreover, they don’t have gluten and present a high nutritional value.